Donor artery stenosis interactions with diastolic blood pressure on coronary collateral flow in type 2 diabetic patients with chronic total occlusion - Shen, Ying (Cardiovasc Diabetol, 2018)
BACKGROUND: We investigated whether and to what extent stenosis of predominant collateral donor artery (PCDA) affects coronary collateral flow in relation to blood pressure (BP) in type 2 diabetic patients with chronic total occlusion (CTO). METHODS: Collateral flow index (CFI) as derived from intracoronary pressure distal to occluded segment and mean aortic pressure in 220 type 2 diabetic patients and 220 propensity score matched non-diabetic controls undergoing percutaneous coronary intervention for CTO. The severity of PCDA stenosis was graded according to lumen diameter narrowing. RESULTS: CFI decreased stepwise from mild to severe stenosis of the PCDA and was lower in diabetic patients with moderate or severe PCDA stenosis than in non-diabetic controls (0.36 ± 0.10 vs. 0.45 ± 0.08, P < 0.001; 0.29 ± 0.09 vs. 0.35 ± 0.08, P = 0.008). When the PCDA was mildly stenotic, CFI increased initially along with a reduction in diastolic BP, and decreased when diastolic BP was below 60 mmHg in diabetic patients (0.38 ± 0.16 vs. 0.57 ± 0.09, P < 0.001). In the presence of moderate PCDA stenosis, diabetic patients had significantly lower CFI compared to non-diabetic controls, with a relative reduction of 19.8% at diastolic BP 70–79 mmHg, 28.2% at 60–69 mmHg and 38.2% below 60 mmHg (all P < 0.05). A severe PCDA stenosis resulted in a more pronounced decrease in CFI, with a relative reduction of 37.3% for diabetics compared to non-diabetics when diastolic BP was below 60 mmHg (P = 0.050). CONCLUSIONS: In the setting of CTO, donor artery stenosis confers greater risk for reduced coronary collateral flow when diastolic BP is decreased. Even a moderate stenosis in the PCDA may be associated with lower collateral flow as diastolic BP decreases below 80 mmHg in type 2 diabetic than in non-diabetic patients.